Оптимізація енергоспоживання системи кондиціювання повітря в тваринницьких приміщеннях - Чміль, А. І. (Енергетика і автоматика, 2017)
OPTIMIZATION OF ENERGY CONSUMPTION OF THE AIR CONDITIONING SYSTEM IN ANIMAL HOUSINGA. Chmil        The productivity of animals, provided that they are fully fed, reaches a high level only when creating a microclimate that meets their biological needs. Reducing the weight gain of animals as a result of an uncomfortable microclimate not only reduces the usefulness of feed energy, but also increases the fattening period, additional lighting of premises, and the use of process equipment, lack of production on occupied production areas, etc.Comfortable parameters of the microclimate (temperature, relative humidity and air speed, as well as the temperature of the surrounding surfaces), in which the production of livestock products is most economical, may have different meanings depending on age, mass and breed of animals, energy content of feeds, heat-insulating properties of lukewarmness and behavior of animals .           The purpose of the research is to justify the optimization model of air conditioning in livestock buildings.Air conditioning in livestock buildings during the year requires high energy costs. Thus, for the model of cattle fattening cattle cattle for 12 thousand animals, the cost of electricity for microclimate alone is 1.29 GJ per 1 cent. Of growth, which is equal to 87.2 % of the total electricity consumption. In view of this, the problem of increasing the energy efficiency of the microclimate system by determining the optimal modes of air conditioning system, creation of its new types, the use of which will save fuel and energy and material resources, becomes actual.The solution of this problem is possible due to the application of the mathematical model of the system of formation of thermal comfort in animals premises.In the process of constructing animal models, a biological regulated system is considered, where the formation of boundary conditions for heat and mass transfer is determined by biological laws, and the external heat transfer is subjected to the physical laws of heat and mass transfer and can be described by their help. In general, the model of the phenomena under consideration can be depicted in the form of a dependence, which combines the thermophysical and physiological patterns of the influence of the environment on the organism of the animal.An effective method of  bioenergetic assessment of the microclimate state in livestock buildings is the definition of  kK, which characterizes the efficiency of the conversion of energy, which is introduced into the life support system, into the energy of the products formed.On the basis of the developed mathematical model, the efficiency of energy costs is determined depending on the parameters of the microclimate (temperature, relative humidity, air velocity and temperature of the internal surfaces of the fence). It was established that in the winter period of the year, the air temperature in the cattle-breeding room for fattening cattle from the bioenergetic point of view should be within the range of +10 - +5 °С and with the decrease of temperature and increase of humidity of external air is reduced. This allows to reduce the cost of thermal energy for a microclimate with a constant coefficient of bioenergy efficiency.